The Psychological Study of Religious Violence: A Theoretical and Methodological Discussion - Tomas Lindgren (Graduate Program of Pontianak Institute of Islamic Studies, 2016)
The aim of this article is to discuss the use and usefulness of psychological theory and psychological methods in the study of religious violence. My analysis of previous research revealed an imbalance between data, method and theory. There are few psychological studies on religious terrorism based on first-hand empirical data. The analysis also showed that psychological explanations of religious terrorism are, in general, not sensitive to cultural factors. Religious terrorism is a culturally constituted phenomenon. It is therefore important that research on religious violence is based on theoretical and empirical approaches sensitive to the cultural construction of violence. This means that psychologists of religion must be willing to use novel and creative methods sensitive to the unique cultural context where the violent behaviour is acted out and interpreted by the actors of the violent drama, for example, discourse analysis or narrative research. In the self-corrective and growth-inducing feedback process between these methods and primary data it would be possible to develop valid psychological explanations of religious violence.